Issues of psychology and pedagogy in the Lithuanian period press of the early 20th century - Gučas, A. (Psichologija, 1962)
After the revolutionary events of 1905-1907, czarism made some concessions in the field of folk education. Although instruction was held in Russian at primary schools, Lithuanian was allowed as a subject. The number of printed books and newspapers increased and periodic press intended for teachers addressing the issues of psychology and pedagogy appeared. The majority of articles of the Mokykla (School) magazines are united by an abstract idea of freedom, an illusion that free education may liberate people from the bonds of czarism and the Orthodox Church. It was demanded that the next generation of humanity – children – were provided with conditions to disclose independently their spiritual gifts, were able to seek freedom, etc. A broad response was received by some ideas of the French bourgeoisie revolution herald Rousseau and individualism of E. Kei. Sometimes they remembered Komensky, his demands to have regard to one’s nature. A great effect was made by the thoughts of Ushinsky, new searches in the education field by S. Shatsky, and Russian experimental pedagogy. In order to make a child’s education consistent with one’s innate characteristics, it was necessary to investigate them. Therefore, issues on the peculiarities of a child’s psyche, possibilities of the development and education thereof were raised – these were the problems that we had already encountered in works of the Lithuanian publicists of the late 19th century. Great attention to the issues of mental development was paid by Vydūnas in the Jaunimas magazine (1910-1914) and his separate books. These issues were extensively discussed in the Mokykla magazine by the teachers I. Burba, A. Jakučionis, I. Palukaitis, and especially, K. Skabeika. But we will not find a single common system of pedagogical or psychological views. A lot of contradictions may be found among different authors and even among different articles by the same author. Vydūnas treated a child’s psychological development as an improvement process, not void of internal contradictions. Vydūnas, A. Jakučionis, and K. Skabeika also recognized the role of activity in a child’s mental development. Besides, Vydūnas noticed that teaching had great importance for a child’s mental development, because it helped find out laws of the objective reality and allowed to affect it at the same time. Human nature improves in thinking and at work. Although a general philosophical conception by Vydūnas is idealistic; he adhered to the positions of intuitionism when solving issues of knowing the reality, and he expressed a number of correct and interesting thoughts on separate issues of a child’s mental development. The Mokykla magazine (1909-1913) published a number of articles criticizing the czarist school for the prevalence of scholastic teaching methods, disregard to children’s innate characteristics, suspension and distortion of their development. A child’s mental development was frequently treated as a spontaneous “disclosure” of innate rudiments. Some authors failed to liberate themselves from the effect of biological evolutionism and cultural historicism. A different attitude towards a child’s mental development raised objections on pedagogical issues. Supporters of children’s spontaneous mental development (Jakučionis, Palukaitis, Skabeika, etc.) stressed that teaching must develop a child’s abilities, independence of one’s thinking so that a teenager going into life could find proper objects of knowledge and goals of activity. Vydūnas, A. Busilas, I. Širvydas, etc., despite recognizing the independence of a child’s solutions and actions during teaching, at the same time also stressed the role of scientific knowledge for general mental development. Busilas solved this contraposition by highlighting the importance of students’ activeness in the education process. Without such activeness, neither formal, nor material education may give noticeable results. No one, however, raised an issue about how in principle it is wrong to oppose the acquisition of knowledge against the development of mental abilities. The demand that education must the meet the needs of children’s nature, age peculiarities had a positive effect on the preparation of textbooks for Lithuanian schools, as well as for solving issues of readings for children. Jakučionis, Palukaitis, Skabeika, etc. take an important place in developing a psychological and pedagogical thought in Lithuania in the early 20th century, because they sharply criticized the czarist Russia, raised a thought on the singularity of a child’s mental life and disclosed some laws of one’s mental development, spread scientific knowledge on experimental pedagogy and psychology. Their demand to harmonize education with the child’s psychic nature prompted teachers to better understand child psychology and sometimes to study it independently.